2018
DOI: 10.1111/ceo.13155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NADPH oxidase 1 and 4 blockade in activated human retinal endothelial cells

Abstract: Our findings in experiments on activated human retinal endothelial cells provide translational corroboration of studies in experimental models of retinal vasculopathy and support the therapeutic application of Nox4 inhibition by GKT136901 and GKT137831 in patients with retinal vascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…The isoforms, NOX1, NOX2, NOX4, and NOX5 were found in endothelial cells. In the retina, NOX1, NOX2, and NOX4 are the most well-studied isoforms [ 74 , 75 , 76 , 77 , 78 ]. NOX2, known as gp91phox, was the first NOX isoform to be identified and the most studied one in the research field of DR [ 79 ].…”
Section: Pathophysiological Role Of Ros In the Retinal Vasculaturementioning
confidence: 99%
See 2 more Smart Citations
“…The isoforms, NOX1, NOX2, NOX4, and NOX5 were found in endothelial cells. In the retina, NOX1, NOX2, and NOX4 are the most well-studied isoforms [ 74 , 75 , 76 , 77 , 78 ]. NOX2, known as gp91phox, was the first NOX isoform to be identified and the most studied one in the research field of DR [ 79 ].…”
Section: Pathophysiological Role Of Ros In the Retinal Vasculaturementioning
confidence: 99%
“…Blockade of NOX4 by the NOX4 inhibitors, GKT136901 and GKT137831, significantly reduced ROS levels and cell death in retinal endothelium. Hence, NOX4 may be considered as a potential therapeutic target in patients with retinal vascular diseases [ 78 ].…”
Section: Pathophysiological Role Of Ros In the Retinal Vasculaturementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we showed that GPER opposed the effects of Ang II by downregulating Nox4 at the transcriptional level and restoring catalase activity. These findings have important implications since randomized clinical trials fail to significantly inhibit oxidative stress using currently available antioxidants such as vitamin E (4143), while preclinical studies with Nox1 and 4 inhibitors (44, 45) are promising. Since oxidative stress is detrimental to cardiovascular tissues, GPER may provide a novel target for inhibition of vascular ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Tellios et al 7 used primary human trabecular meshwork cells to show that the gap junction protein, connexin43, may be a marker of trabecular meshwork stretch‐related injury in primary open‐angle glaucoma. Appukuttan et al 8 worked with primary retinal vascular endothelial cells, as well as cells that were immortalized by transfection with human papillomavirus genes, to study novel inhibitors of enzymes that produce reactive oxygen species, with implications for the treatment of retinal vascular diseases. In addition, human ocular tissue may be grown in the dish or dissected fresh from human eyes for research projects.…”
mentioning
confidence: 99%